Digital technologies in the care of people with diabetes during the COVID-19 pandemic: a scoping review - Francisca Diana da Silva Negreiros; Açucena Leal de Araújo; Samuel Miranda Mattos; Tatiana Rebouças Moreira; Virna Ribeiro Feitosa Cestari; Lucilane Maria Sales da Silva; Thereza Maria Magalhães Moreira (SciELO, 2021)
Abstract Objective: To map evidence on the use of digital technologies in the care of people with diabetes during the COVID-19 pandemic. Method: This is a scoping review, based on the JBI manual, which included scientific articles and gray literature from nine primary and seven secondary databases. Articles were independently assessed by two reviewers. Rayyan® was used to select the studies. The description of study characterization is presented in a table and tables, ending in a narrative synthesis. Results: A total of 1,964 studies were identified and, after selection, 23 publications remained for analysis. It turned out that telemedicine was used in all studies and remote consultation support technologies included continuous glucose monitoring devices, glucose data analysis software, insulin delivery systems, applications, audio and/or voice communication devices, which facilitated remote diabetes mellitus monitoring and management. Conclusion: Telehealth, monitoring technologies, insulin delivery systems and communication devices were tools used to monitor patients with diabetes during the pandemic.